Exploring the Visual-Tactile Temporal Binding Window and Multisensory Influences on Sensorimotor Synchronization - Huntley, Michelle Kaye (Curtin University, 2024)
Meaningful interaction with our environment relies upon timely integration of multisensory information and actions performed in synchrony with sensory input. This thesis examines the temporal binding window for visual-tactile integration using the simultaneity judgement task, and the influence of multisensory information on sensorimotor synchronization. Additionally, this thesis investigates functional connectivity between unisensory and multisensory neural regions during, and immediately following stimulus presentation, in the simultaneity judgement task to understand differences between simultaneous and non-simultaneous perception